2010
DOI: 10.3109/08039488.2010.545144
|View full text |Cite
|
Sign up to set email alerts
|

Sexual self-perception in schizophrenic and depressive patients

Abstract: We can conclude that patients suffering from schizophrenia or depression differ from healthy individuals in all of the aspects of sexual self-perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This is consistent with a recent report by Vucic-Peitl, Peitl and Pavlovic (2011), which found that when compared to a healthy control group, people with either schizophrenia or depression scored significantly higher on sexual incompetence and significantly lower on sexual satisfaction, and that these two diagnosed groups were not significantly different from one another.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a recent report by Vucic-Peitl, Peitl and Pavlovic (2011), which found that when compared to a healthy control group, people with either schizophrenia or depression scored significantly higher on sexual incompetence and significantly lower on sexual satisfaction, and that these two diagnosed groups were not significantly different from one another.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies looked at variables that might hinder intimate relationships for individuals with a psychotic disorder. Sexual dysfunction resulting from medication side effects (even though we eliminated many studies looking at sexual dysfunction in pharmacological studies) and psychiatric symptoms, history of abuse, poor sexual self-concept and low self-esteem/confidence, attachment insecurities, limited resources (intimacy skills and financial means), and internalized stigma were all linked to romantic and/or sexual difficulties (Ben Mahmoud et al, 2013; Huguelet et al, 2015; Halouani et al, 2018; Peitl, Peitl, & Pavlović, 2011; Pillay, Lecomte, & Abdel-Baki, 2018; Sarısoy et al, 2013; Stewart, Lysaker, & Davis, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other factors such as religious perspectives can affect sexual function and sexual self-concept in mentally ill patients. Religion as a social institution, including religious beliefs, ceremonies and religious activities, and a sense of belonging to a religious community plays a main role in the reconstruction and recovery in individuals with the mental illness (22, 39). Spirituality and religion compared with secular coping strategies, answer for incompetence and inadequacy in the human being.…”
Section: Resultsmentioning
confidence: 99%
“…Taking refuge in religion has a relationship with a better understanding of and compliance with the illness and drug use. Therefore, less religious patients experience more, the symptoms associated with depression (22, 39). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation